Riset Cerdas di Era Digital: Pemanfaatan AI, SLR dan ZOTERO dalam Penulisan Ilmiah untuk Mahasiswa - Roy Mubarak; Mubarak, Roy; Asruddin; Wawan Sismadi; Imam Riadi; Rusydi Umar (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The rapid digital transformation requires students to possess efficient and structured research literacy. This Community Empowerment Program (Prodamat) aims to enhance the research capacity of students at Politeknik Mitra Karya Mandiri through a "Smart Research in the Digital Era" approach. The activity was conducted utilizing a participatory training and mentoring method focusing on three main pillars: Systematic Literature Review (SLR) methodology, ethical Artificial Intelligence (AI) utilization, and the mastery of scientific publication tools. The implementation process included comprehensive guidance on defining research questions using the PICOC framework, leveraging AI-based search tools like Elicit and Semantic Scholar with strict adherence to the Human-in-the-Loop principle to mitigate AI hallucinations, and integrating reference management software such as Zotero and Publish or Perish. The results indicate a significant improvement in students' understanding and technical skills in extracting literature data, measuring publication impact, and automating reference management. In conclusion, the integration of the SLR method, ethical AI utilization, and digital reference tools optimally enhances the efficiency and quality of students' scientific writing while strictly maintaining academic integrity for future publications.